If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 9y + -4 + z Reorder the terms: 5 + 3x = 9y + -4 + z Reorder the terms: 5 + 3x = -4 + 9y + z Solving 5 + 3x = -4 + 9y + z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = -4 + 9y + -5 + z Combine like terms: 5 + -5 = 0 0 + 3x = -4 + 9y + -5 + z 3x = -4 + 9y + -5 + z Reorder the terms: 3x = -4 + -5 + 9y + z Combine like terms: -4 + -5 = -9 3x = -9 + 9y + z Divide each side by '3'. x = -3 + 3y + 0.3333333333z Simplifying x = -3 + 3y + 0.3333333333z
| a+a+7=3+a | | 3[4(3x+1)-(10x-9)]=7x+9 | | x=2y^2-4 | | (2x-3)/4=(3-2x)/6 | | 2x-(1/x)=1 | | x^2-x-x=0 | | 2X+7X-12=33 | | X^2-2x-12=-12 | | 7(t-6)+7t=7(2t+3)-10 | | -6=(y-4)/9 | | 1/2(4y+3)=1/4(y+8) | | 7y+12/t=36 | | 61=6x-11 | | 3(2x+1)+13x-12=18x-3 | | -1=x/3-7 | | 2-6x=-88 | | 16=6x+40 | | -(4y+2)-(-3y-8)=2 | | 4x+20=(x+3) | | 15d+2=9d+26 | | -7x^2-57x-8=0 | | 5z+(6+2z)=-43 | | 9/7t=-7/2 | | 3(a+8)=33.6 | | 1.5x+1=5-2x | | 49/7x60/2x5 | | 15x+(x+2)=10+6x+(-x+3) | | X/p+x/q=a | | 1/2(2t+3)=2/3(6t-1) | | 16=7x | | 3/2x+1=5-2x | | 3=2c-4 |